2022
DOI: 10.3389/fcvm.2022.943633
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound-guided treatment for heart failure: An updated meta-analysis and trial sequential analysis

Abstract: BackgroundThe usefulness of lung ultrasound (LUS) in guiding heart failure (HF) treatment is still controversial.PurposeWe aimed to evaluate the usefulness of LUS-guided treatment vs. usual care in reducing the major adverse cardiac event (MACE) rate in patients with HF.Materials and methodsWe performed a systematic review and meta-analysis of randomized controlled trials (RCTs) identified through systematic searches of MEDLINE, EMBASE, the Cochrane Database, Google Scholar, and SinoMed. The primary outcome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, no significant differences in death rates were observed [46,47,55]. Additionally, LUS-guided treatment was associated with a lower risk of Major Adverse Cardiac Events (MACEs) [59,60]. Nonetheless, while LUS improved fluid status with a significantly greater reduction in the number of B-lines during the first 48 hours, it did not reduce heart failure readmission [53,55,62].…”
Section: Resultsmentioning
confidence: 98%
“…However, no significant differences in death rates were observed [46,47,55]. Additionally, LUS-guided treatment was associated with a lower risk of Major Adverse Cardiac Events (MACEs) [59,60]. Nonetheless, while LUS improved fluid status with a significantly greater reduction in the number of B-lines during the first 48 hours, it did not reduce heart failure readmission [53,55,62].…”
Section: Resultsmentioning
confidence: 98%
“…However, no significant differences in death rates were observed [55][56][57]. Additionally, treatment guided by lung ultrasound (LUS) was linked to a reduced risk of Major Adverse Cardiac Events (MACEs) [58,59], and a significantly greater reduction in the number of B-lines during the initial 48 h, but it did not reduce heart failure readmission [57,60,61]. (4) The results of LUS remained independent of NT-proBNP levels [32,43,50,62].…”
Section: Resultsmentioning
confidence: 99%
“…46 A recent meta-analysis showed that LUS can help guide volume management in HF patients and reduce risk of readmission. 47,48 Although evidence suggests a benefit for LUS-guided therapy in the management of HF patients, additional studies are needed to assess the impact on survival, which decreases with each subsequent HF hospitalization, as well as hospital quality metrics and reimbursement. [49][50][51] There are several limitations of this study.…”
Section: Discussionmentioning
confidence: 99%